Labour reallocation, relative prices and productivity - Shutao Cao; Danny Leung (Bank of Canada, 2010)
This paper documents the rate at which labour flows between industries and between firms within industries using the most recent data available. It examines the determinants of these flows and their relationship with the productivity growth. It is found that the dispersion of industry employment growth rates has been elevated since 2005, and that this increase is not likely to be related to the business cycle. It is also found that changes in real exchange rates and commodity prices can account for a significant part of the employment dispersion across industries, especially since 2005. However, shifts of employment labour between industries have generally not contributed positively to aggregate labour productivity growth. With respect to movements of labour between firms within industries, it is found that the job reallocation rates have fallen steadily over the past decade and a half. Finally, unlike labour flows between industries, excess job reallocation rates within industries are found to be strongly related to multifactor productivity and labour productivity growth at the industry level.
Keywords: D23; J6; E32; 330; Productivity; Inflation and prices; Labour markets; Arbeitsmobilität; Konjunktur; Unternehmensentwicklung; Inflationsrate; Wechselkurs; Produktivität; Kanada